Chopin’s Dream in George Sand’s Memoir - Palandrani, Tiziana (Eikón / Imago, 2022)
This work aims to analyse Chopin’s dream - as recounted by George Sand in the last volume of Histoire de ma vie - from the point of view of the writer’s literary production, and also of the artistic-literary context of the time in which her autobiography was published. The general analysis of her work shows a recurrence of topical motifs; among all, the theme of the death in the water emerges from the first to the last productions, including the narrative about Chopin, highlighting aesthetic coincidences with some paintings of the time (in particular with the Ophelia by Millais, depicted with the body floating in water, not yet submerged but in a near-death condition). Reflecting on the intense impact that George Sand’s writings will later have on the reception of the composer’s image, this article aspires to examine some aspects that will accompany Fryderyk Chopin’s pictorial and literary portrayal, suggesting the hypothesis that the chronicle of the Chopinian dream could be influenced more by poetic devices than by a total adherence to the reality of the facts.